Quranic understanding among non-native speaker of Arabic: Malaysian experts’ perspectives - Hazleena Baharun; Hishomudin Ahmad; Saadah Abd Rahman; Noor Saazai Mat Saad; Ikmal Hafiz Jamal (Universiti Kebangsaan Malaysia Press, 2024)
Indexed by Scopus